The Concept Of Scientific Theory And Its Importance In Psychology - Mallayeva Hilola Isroilovna (Euro Asian Journal Publishing, 2025)
This is an article on the theory of scientific theory, its role in science and its practical significance. A scientific theory is a set of assumptions that serve to explain and predict phenomena. In psychology, these theories provide a fundamental theoretical basis for understanding the complexities of human behavior and consciousness.
Keywords: scientific theory; psychology; hypothesis